Moving Morality Beyond the In-Group: Liberals and Conservatives Show Differences on Group-Framed Moral Foundations and These Differences Mediate the Relationships to Perceived Bias and Threat - Stewart, Brandon D.; Morris, David S. M. (Frontiers in Psychology, 2021)
Moral foundations research suggests that liberals care about moral values related to individual rights such as harm and fairness, while conservatives care about those foundations in addition to caring more about group rights such as loyalty, authority, and purity. However, the question remains about how conservatives and liberals differ in relation to group-level moral principles. We used two versions of the moral foundations questionnaire with the target group being either abstract or specific ingroups or outgroups. Across three studies, we observed that liberals showed more endorsement of Individualizing Index (Harm and Fairness foundations) with an outgroup target, while conservatives showed more endorsement of Binding Index (Loyalty, Authority and Purity foundations) with an ingroup target. This general pattern was found when the framed, target-group was abstract (i.e. ‘ingroups’ and ‘outgroups’ in Study 1) and when target groups were specified about a general British-ingroup and an immigrant-outgroup (Studies 2 & 3). In Studies 2 and 3, both Individualizing-Ingroup Preference and Binding-Ingroup Preference scores predicted more Attitude Bias and more Negative Attitude Bias toward immigrants (Studies 2 & 3), more Implicit Bias (Study 3), and more Perceived Threat from immigrants (Studies 2 & 3). We also demonstrated that increasing liberalism was associated with less Attitude Bias and less Negative Bias toward immigrants (Studies 2 & 3), less Implicit Bias (Study 3), and less Perceived Threat from immigrants (Studies 2 & 3). Outgroup-individualizing foundations and Ingroup-Binding foundations showed different patterns of mediation of these effects.